Addressable, Stretchable Heating Silicone Sheets. Issue 9 (2nd August 2019) - Bilodeau, R. Adam; Yuen, Michelle C.; Kramer‐Bottiglio, Rebecca
Abstract: Research into new active materials for soft robots has generated promising new thermally responsive materials for functions such as variable stiffness, on‐demand shape change, and actuation. These new thermally responsive materials require a form of addressable thermal control that is compliance‐matched to its host system. In response to this need, this work presents stretchable, addressable heating silicone sheets that can control soft, thermally responsive materials. The sheets are created using layer‐by‐layer deposition of a bulk conductive elastomer that can be Joule heated, with embedded liquid–metal microchannels used as electrodes. This combination allows the bulk, addressed material to be stretched and twisted while in operation. Local, addressable heating is demonstrated in a silicone‐based composite that is capable of cyclic strains of up to 40%, while still self‐heating to over 100 °C. The heating sheets are demonstrated as a thermal control platform in both color changing and stretch‐and‐hold operations using all silicone‐based composites. Additionally, this platform is bonded to a variable‐stiffness polymer that, with its selective heating capability, enables folding at targeted locations. Abstract : An addressable, stretchable heater made of conductive silicone composite is coupled with thermally‐responsive materials to enable localized modulus changes. The reinforced composite silicone with liquid metal electrodes creates an addressable, Joule‐heating system that acts as both a robust thermal display and thermal control for targeted softening of an adjacent body. This is demonstrated through both planar folding and stretch‐and‐hold shape change.